Investigating language as social (Inter-)Action the 15th Conference on British and American Studies - Burada, Marinela; Tatu, Oana; Sinu, Raluca (Cambridge Scholars Publishing, 2019)
This volume consists of papers presented during the 15th Conference on British and American Studies, held at Transilvania University of Braşov, Romania. It reflects the work conducted by senior and junior researchers on a range of interesting topics falling into the wider scope of cognitive linguistics, language contact, translation and lexicography. The investigations reported here are streamlined into three chapters. The first, "Native Language Explorations and Acquisition", has Romanian as its central theme.